Essentials of stem cell biology - Lanza, Robert; Atala, Anthony, 1958- (Academic Press, 2014)
This book combines the prerequisites for a general understanding of adult and embryonic stem cells with a presentation of the latest research information about specific organ systems. It covers a wide range of topics, including basic biology/mechanisms, early development, ectoderm, mesoderm, endoderm, and methods to the application of stem cells to specific human diseases, regulation and ethics, and patient perspectives.